The Influence of Quality of Umrah Package Services on the Interest of Jama'ah to Register at PT Cordoba Berkah Mandiri - Nugroho, Muhammad Habib; Nurani, Khadijah (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2023)
Although PT. Cordoba Berkah Mandiri has a license to operate legally, the products are not innovative and varied, and the information presented is not complete and detailed. This study aimed to determine and analyze how much influence the quality of Umrah service package services has on the congregation's interest in registering at PT Cordoba Berkah Mandiri.This research is a quantitative research that analyzes the relationship between variables by testing the hypothesis. The data collection technique was a questionnaire (questionnaire) with a sample of 91 people. The data analysis technique used is simple regression analysis, T-test, and coefficient of determination test (R2). The results of the regression analysis show that the service quality variable (X) has a positive and significant influence on the intention to register (Y) in choosing travel organizers for the Umrah pilgrimage as evidenced by the equation Y = 12.315 + 0.459X, meaning that before there is a service quality variable, the value of interest in registering amounted to 12.315 or 1231.5%, but after there was a service intensity variable, interest in registering increased by 0.459 or 45.9%. In terms of service quality, it also positively and significantly influenced interest in registering with travel organizers of the Umrah pilgrimage.